Literature Review on the Role of Digital Transformation in Improving Organizational Performance - Effy Zalfiana Rusfian; Ary Subiyantoro; Aries Widya Gunawan (Rey Media Grafika, 2024)
Digital transformation has become a key factor in improving organizational performance in the modern era. This study aims to conduct a systematic literature review on the role of digital transformation in enhancing operational efficiency, innovation, and customer satisfaction. The findings reveal that adopting technologies such as big data, cloud computing, the Internet of Things (IoT), and artificial intelligence can boost productivity, accelerate data-driven decision-making, and create new value for customers. However, the process faces challenges, including resistance to change, high investment costs, and data security risks. Key success factors include digital leadership, organizational readiness, and effective change management. This review provides strategic insights for organizations to develop successful digital transformation initiatives and identifies opportunities for future research in diverse industrial and geographical contexts.